2004
DOI: 10.1128/jb.186.9.2766-2773.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bdellovibrio bacteriovorusStrains Produce a Novel Major Outer Membrane Protein during Predacious Growth in the Periplasm of Prey Bacteria

Abstract: Bdellovibrio bacteriovorus is a predatory bacterium that is capable of invading a number of gram-negative bacteria. The life cycle of this predator can be divided into a nonreproductive phase outside the prey bacteria and a multiplication phase in their periplasm. It was suggested that during the reproduction phase, B. bacteriovorus reutilizes unmodified components of the prey's cell wall. We therefore examined the outer membranes of B. bacteriovorus strains HD100 (DSM 50701) and HD114 (DSM 50705) by using Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…As other proteins of the predator, including the strongly expressed cytoplasm-located elongation factor Tu (17), flagellin, and other molecules focusing in different parts of the gels were not detected, we are confident in ruling out contamination by a low level of remaining bdellovibrio attack-phase cells in the ghost envelope fraction. The polypeptide identified in this study is highly homologous to a new, recently described OMP from B. bacteriovorus type strain 100 (2).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…As other proteins of the predator, including the strongly expressed cytoplasm-located elongation factor Tu (17), flagellin, and other molecules focusing in different parts of the gels were not detected, we are confident in ruling out contamination by a low level of remaining bdellovibrio attack-phase cells in the ghost envelope fraction. The polypeptide identified in this study is highly homologous to a new, recently described OMP from B. bacteriovorus type strain 100 (2).…”
Section: Discussionmentioning
confidence: 78%
“…4a), suggesting that it originated from the bdellovibrio predator. Extraction and mass spectrometric analysis of this polypeptide revealed that it was derived from the predator ( Table 1) and was related to a recently described OMP from B. bacteriovorus type strain 100 (2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations